(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
In the face of the globalization of risk society and the increasingly serious ecological crisis, the international community proposed to formulate the ecocide in the Rome Statute in response to the public’s physical security. However, the environmental legal interest is abstract, and the responsibility of the infringer of legal interest is difficult to distinguish. The reckless formulation of the ecocide leads to the absence of legal interest protection mechanism, which is symbolic legislation. Symbolic legislation, in order to reflect legislators’ concern for social issues, is very easy to subvert the theoretical system of the Rome Statute based on freedom and behavior, so that damages its human rights protection function. Dogmatik has the function of explaining law, criticizing and guiding legislation. Through the etymological interpretation of the doctrine, this paper puts forward the axiomatic dogmatik and clarifies the structure of dogma - overall norms - specific norms - criminal law knowledge - specific cases within the axiomatic dogmatik. And this structure provides a path for the criminalization of ecocide: The basic value of the Rome Statute lies in the protection of human well-beings and the right to life (axiomatic dogma), and the protection of environmental rights should take human well-beings and the right to life as the boundary (specific legal interests); Include typical ecological acts such as land encroachment and serious environmental pollution that violate human well-beings and right to life into genocide and crimes against humanity closely related to them (specific norms/criminal law knowledge); It can not only curb the ecocide, but also maintain the internal coordination and external stability of the Rome Statute. Key words: symbolic legislation, criminal law function, dogmatik, legal interest